The home literacy environment as a predictor of the early literacy development of children at family-risk of dyslexia - Snowling, M; Hamilton, L; Hulme, C; Hayiou-Thomas, M (Taylor and Francis, 2016)
The home literacy environment (HLE) predicts language and reading development in typically developing children; relatively little is known about its association with literacy development in children at family-risk of dyslexia. We assessed the HLE at age 4 years, precursor literacy skills at age 5, and literacy outcomes at age 6, in a sample of children at family-risk of dyslexia (n=116) and children with no known risk (n=72). Developmental relationships between the HLE and literacy were comparable between the groups; an additional effect of storybook exposure on phoneme awareness was observed in the family-risk group only. The effects of SES on literacy were partially mediated by variations in the HLE; in turn, effects of the HLE on literacy were mediated by precursor skills (oral language, phoneme awareness and emergent decoding) in both groups. Findings are discussed in terms of possible gene-environment correlation mechanisms underpinning atypical literacy development.